Madrasah, Surau, dan Pasar Sepanjang Jalur Kereta Api Kawasan Warisan Tambang Batu Bara Ombilin Sawahlunto - Wimra, Zelfemi; Nasir, Muhammad; Bunaiya, Mahlil (Puitika, 2024)
The existence of the Ombilin Sawahlunto coal mine not only generates economic income from mining operations but also produces socio-cultural impacts. The various effects can be seen in education, religion, arts, and regional infrastructure. This paper explores the influence of the Ombilin Sawahlunto coal mine, focusing on education and the traditional economy. The railway line connecting Padang to Sawahlunto is a means of mobility of knowledge and education, seen in the establishment of madrasahs and surau as religious education centers. Likewise, traditional markets provide commodities from various regions to be distributed to other areas. The mobility of knowledge and commodities influence the spread of multiple receptions and the formation of culture, which results from the interaction and mobility of society, goods, and discourse supported by the existence of the coal mine in Sawahlunto.